Pengaruh Current Ratio (Cr), Total Asset Turnover (Tato) Dan Return On Equity (Roe) Terhadap Laba Pada Pt. Nusantara Medika Utama Mojokerto Periode Tahun 2021-2025 - Hesti Dwi Puspita Sari; Nurdiana Fitri Isnaini; Marisha Khanida (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2022)
The purpose of this study is to examine and analyze the influence of the Current Ratio (Liquidity), Total Asset Turnover (Profitability), and Return on Equity (Profitability) on Profit PT. Nusantara Medika Utama Period 2016-2020. This study uses historical data from the financial statements of PT. Nusantara Medika Utama Period 2026-2020. The data analysis method used is multiple linear regression model with SPSS20 software tools. With the results of the Current ratio and Total Asset Turnover have a significant effect on profit, but Return on Equity has no significant effect on profit.